Implementing ‘Vivir Bien’: Results and Lessons from the Biocultura Programme, Bolivia - Frédérique Weyer (Revue Internationale de Politique de Développement)
In Bolivia, an alternative vision of development has emerged that relies on the concepts of Madre Tierra (Mother Earth) and Vivir Bien (Living Well), and promotes balance and harmony between humans and nature. It aims to break away from the economic model previously adopted by Bolivia, a model that has made the country highly dependent on the export of raw materials. This chapter analyses the Biocultura programme, a project launched in 2008 by the Government of the Plurinational State of Bolivia and the Swiss Agency for Development and Cooperation (SDC), which aims to translate this alternative vision of development into concrete practices. Stemming from a participatory approach, this initiative shows that it is possible to reconcile the conservation of biodiversity with raising incomes and the promotion of local knowledge. It also contributes to the creation and strengthening of institutions and policies in line with Vivir Bien. This chapter is based on documents and ideas developed by the Biocultura programme and the SDC, as well as on fieldwork carried out between 2013 and 2015.